Effect of internal corporate social responsibility activities on tourism and hospitality employees ‘normative commitment during COVID-19 - Tarek Sayed AbdelAzim; Ayman Kassem Ayman Kassem; Abdallah Alajloni; Abdullah Alomran; Ahmed Ragab; Eman Shaker (Tourism & Management Studies)
The purpose of this research is to explore the extent to which internal corporate social responsibility activities affect employees’ normative organizational commitment during the COVID-19 crisis and to survey the role of the administrative level as a moderator between the two of them. A survey in the form of a self-completed questionnaire was conducted on a sample of employees in hospitality and tourism establishments in Hail city, Kingdom of Saudi Arabia. 213 employees voluntarily participated in the current study. Their responses were examined by using linear regression and exploratory factor analyses. The findings revealed that internal corporate social responsibility is a positive predictor of normative organizational commitment. The total effect of internal corporate social responsibility on normative organizational commitment could not be enhanced through the moderation of the administrative position. This study has important implications for both academics and professionals. Theoretical and managerial implications, contributions, limitations, and future study objectives were reviewed in light of the findings.